(untitled) (Revista Innova Educación, 2019)
The central objective of this work is to construct the graph of bivariate, in turn curved shows of contour and you curve of level with his respective heights, utilizing commands meshgrid, surf, surfc and contour of the mathematical parcel MATLAB. As a result principal we visualized the graph at a virtual scene 3D.